110 Sex-related differences in clinical presentation and outcome of patients with cardiac transthyretin amyloidosis and light chain amyloidosis. (8th December 2021) - Zampieri, Mattia; Argirò, Alessia; Allinovi, Marco; Tassetti, Luigi; Zocchi, Chiara; Gabriele, Martina; Andrei, Valentina; Fumagalli, Carlo; Di Mario, Carlo; Tomberli, Alessia; Olivotto, Iacopo; Perfetto, Federico; et al.
Abstract: Aims: We aimed to ascertain whether sex-related differences are relevant to the pathophysiology, presentation, and outcomes in different types of cardiac amyloidosis—a field still poorly investigated. Medical files from consecutive patients diagnosed with cardiac amyloidosis between 2000 and 2020, at Careggi University Hospital, were retrospectively evaluated. Methods and results: Over this period, 259 patients (12% females) were diagnosed with wild type transthyretin amyloidosis (wtATTR), 52 (25% females) with hereditary transthyretin amyloidosis (hATTR) and 143 (47% females) with light chain amyloidosis (AL). Wt-ATTR women, compared to men, were significantly older at the time of diagnosis and showed higher National Amyloidosis Centre score, thicker normalized interventricular septum, higher diastolic dysfunction and worse right ventricular function. Females with hATTR and AL had lower normalized cardiac mass compared to men. Otherwise, bio-humoural parameters, NYHA class, and ECG characteristics were similar. No differences in outcome were observed with regard to sex. Conclusions: In conclusion, we did not observe major differences in clinical expression related to sex in different types of cardiac amyloidosis: specifically, outcome was not affected. Nevertheless, women with wtATTR showed a worse profile at diagnosis and evidence suggesting a later recognition of disease compared to men, highlighting the need for a higher index of suspicion in female patients.